2016
DOI: 10.1016/j.anireprosci.2016.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Classification of ostrich sperm characteristics

Abstract: The success of assisted reproduction techniques is dependent on a sound foundation of understanding sperm characteristics to evaluate so as to improve semen processing. This study offers a descriptive basis for ostrich semen quality in terms of sperm function characteristics (SFC) that include motility, measured by computer assisted sperm analysis CASA (SCA(®)), viability (SYBR14/PI) and membrane integrity (hypo-osmotic swelling test). Relationships among these SFC's were explored and described by correlations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
5
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 61 publications
4
5
1
Order By: Relevance
“…Ejaculates collected around the summer solstice as well as spring and autumn equinoxes were highly concentrated and contained higher number of spermatozoa than those collected around the winter solstice. This finding is consistent with previous studies that reported that semen samples collected during the spring, summer and autumn months contain a higher sperm concentration than samples collected in winter (Bonato et al 2014, Smith et al 2016. This suggests that sperm output in ostriches may be influenced by a range of environmental variables such as daylength, rainfall and temperature (Ball and Ketterson 2008).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Ejaculates collected around the summer solstice as well as spring and autumn equinoxes were highly concentrated and contained higher number of spermatozoa than those collected around the winter solstice. This finding is consistent with previous studies that reported that semen samples collected during the spring, summer and autumn months contain a higher sperm concentration than samples collected in winter (Bonato et al 2014, Smith et al 2016. This suggests that sperm output in ostriches may be influenced by a range of environmental variables such as daylength, rainfall and temperature (Ball and Ketterson 2008).…”
Section: Discussionsupporting
confidence: 92%
“…Sperm motility traits were measured using the Sperm Class Analyzer® (SCA) version 5.3 (Microptic S.L., Barcelona, Spain) with a Basler A312fc digital camera (Basler AG, Ahrensburg, Germany) mounted on an Olympus BX41 microscope (Olympus Optical Co., Tokyo, Japan) equipped with phase contrast optics. An aliquot of neat semen at a concentration of 20 × 10 6 sperm cells/mL was diluted in 245 μL of standard motility buffer containing sodium chloride (150 mM) and TES (20 mM) with 2% male specific seminal plasma (Smith et al 2016). The tube containing the diluted semen was placed in an incubator at 38°C for 1 min, before loading 2 μl of the diluent onto a pre-warmed slide (at 38°C ), covered gently with a cover slip (22 × 22 mm) and allowed to settle for 20 s prior to recording.…”
Section: Evaluation Of Sperm Motilitymentioning
confidence: 99%
See 3 more Smart Citations